Antimicrobial Activity of Perspiration Pads and Cotton Cloth Fabricated with the Ethyl Acetate Extract of Eichhornia crassipes (Mart.) Solms. (8th December 2014) - Lalitha, P.; Jayanthi, P.; Sujitha, R.
Abstract : Waterhyacinth is one of the most dangerous aquatic weeds causing various ecological and environmental issues. The plant has several pharmaceutical properties in spite of its harmful nature. In the present study, perspiration pads and cotton cloth fabricated with the ethyl acetate extract of waterhyacinth were evaluated for its activity against Corynebacterium. Perspiration pads and samples of cotton cloth were fabricated with ethyl acetate extract of Eichhornia crassipes by three methods, namely, dipping, sonication, and homogenization. The antimicrobial activity of the fabricated textile materials was tested against Corynebacterium, a microorganism commonly seen in human sweat. Disc diffusion method (AATCC 147) was used for evaluating the antimicrobial nature of the fabricated samples. Sonication was found to be efficient for coating of the extract on the cotton cloth, whereas dipping method was found to be efficient in case of perspiration pads. No bacterial growth was observed under and on the fabricated cloth and perspiration pads indicating that the fabrics possess bacteriostatic property and not bactericidal property and the absence of leaching of the extract. The results showed significant antimicrobial activity of the ethyl acetate extract of Eichhornia crassipes coated onto fabrics against Corynebacterium with no growth under and on the test sample.